Nickel-based single-crystal high-temperature alloy with high structure stability and preparation method thereof
By using precise composition design and preparation process of nickel-based single-crystal superalloys, the problems of microstructure stability and casting processability of single-crystal alloys for heavy-duty gas turbines have been solved, realizing the preparation of low-cost, high-performance single-crystal alloys suitable for heavy-duty gas turbine blades.
Patent Information
- Application Number
- CN202511584990.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-30
AI Technical Summary
Existing single-crystal high-temperature alloys for heavy-duty gas turbines have insufficient structural stability under high-temperature environments, poor casting processability, and high cost, making it difficult to meet the requirements for long-term service.
By using nickel-based single-crystal superalloys, and by precisely proportioning γ' phase-forming elements such as Al, Ta, and Ti with γ phase-forming elements such as Co, Cr, and W, combined with the spiral crystal selection method and three-stage aging treatment, a single-crystal alloy with high microstructure stability and high casting performance was prepared.
It significantly reduces the precipitation temperature of harmful TCP phase, improves microstructure stability and casting performance, reduces manufacturing costs, and achieves a balance between high-temperature mechanical properties and long-term service life, with performance superior to traditional Re-free single-crystal alloys.
Smart Images

Figure CN121428347A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-temperature alloy technology, and in particular to a nickel-based single-crystal high-temperature alloy with high structural stability and its preparation method. Background Technology
[0002] To improve efficiency, modern heavy-duty gas turbines typically have inlet temperatures exceeding 1300°C, approaching the melting point of metallic materials. Turbine blades, as critical hot-end components, are subjected to harsh environments of high temperature, high stress, and high thermal corrosion, facing challenges such as insufficient structural stability, limited temperature resistance, and decreased oxidation resistance, making them prone to premature failure. To adapt to ever-increasing operating temperatures, gas turbine manufacturers both domestically and internationally are continuously committed to developing high-temperature alloy materials with superior performance.
[0003] Among numerous high-temperature materials, single-crystal superalloys exhibit superior high-temperature long-term service potential due to the complete elimination of grain boundaries and a significant reduction in the content of low-melting-point grain boundary strengthening elements. With advancements in alloy design theory and casting processes, especially the introduction of refractory elements such as Re, second-generation single-crystal superalloys, represented by PWA1484, CMSX-4, and René N5, have gradually matured. Their temperature resistance is approximately 30°C higher than that of the first-generation products, and they are currently being used in the manufacture of H-class gas turbine blades.
[0004] The excellent high-temperature performance of single-crystal alloys mainly relies on the addition of large amounts of refractory and rare earth elements such as Re and Ru. However, the introduction of these elements also brings a series of problems. On the one hand, Re resources are scarce and expensive, significantly increasing material costs. On the other hand, high content of refractory elements exacerbates the tendency for defects during the casting process, especially for gas turbine blades with complex shapes and large dimensions, further increasing manufacturing difficulty and cost. In addition, the interaction of multiple alloying elements can easily induce compositional segregation, promoting the precipitation of harmful topologically close-packed (TCP) phases, affecting the stability of the microstructure, and restricting the widespread application of this type of alloy.
[0005] To reduce dependence on retinylamide (Re), international research has been conducted on Re-free single-crystal alloys. For example, ONERA's MD2 alloy, GE's Rene N500 (optimized from Rene N5), and CM's CMSX-7 (improved from CMSX-4), all attempt to achieve the performance levels of second-generation single-crystal alloys without Re. However, these materials still face challenges such as high TCP phase precipitation temperatures and insufficient microstructural stability to meet the requirements of high-temperature, long-term service. Furthermore, their high density and poor casting processability limit their application in large-size blades, resulting in high manufacturing costs.
[0006] In summary, how to ensure high-temperature performance while taking into account structural stability, casting processability, and cost control has become a key technical problem that urgently needs to be solved in the research and development of single-crystal blade materials for heavy-duty gas turbines. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to provide a nickel-based single crystal superalloy and its preparation method, so as to ensure high-temperature performance while taking into account the stability of microstructure, casting processability and cost control.
[0008] To address the above problems, the present invention proposes the following technical solution:
[0009] In a first aspect, the present invention provides a nickel-based single-crystal superalloy with high structural stability, comprising the following chemical composition by mass percentage:
[0010] 5-7% Al, 7.5-10% Co, 5-7% Cr, 0.1-0.2% Hf, 0-2% Mo, 5.5-7.5% Ta, 0-1% Ti, 8-10% W, 0.02-0.05% C, 0.003-0.005% B, balance Ni.
[0011] It should be noted that Cr and Al in the alloy composition have antioxidant properties and need to be at relatively high levels. Hf and Ta help improve casting performance, and Ta also has solid solution strengthening and precipitation strengthening effects. Without adding Re, the addition of Ta needs to be increased, but excessive Ta can easily precipitate harmful TCP phase. W is an important solid solution strengthening element. Without adding Re, the addition of W should be appropriately increased, but too high a content can easily cause TCP phase precipitation; it should be controlled at 8-10%. Co helps reduce the stacking fault energy of the alloy, thereby improving creep performance, but too high a content will lower the solid solution temperature and reduce high-temperature performance. Mo can increase the interdendritic strengthening effect. Al and Ti are γ' phase constituent elements, ensuring precipitation strengthening. In addition, Ti can also improve the alloy's resistance to hot corrosion. C helps form carbides to reduce the porosity of the alloy and provides second-phase strengthening, while B helps increase the tolerance for small-angle grain boundaries.
[0012] The further technical solution includes the following chemical components by mass percentage:
[0013] 5.5-6.2% Al, 8-10% Co, 5.5-6.5% Cr, 0.1-0.2% Hf, 0.5-1.5% Mo, 6-7.5% Ta, 0.5-1% Ti, 8.5-10% W, 0.02-0.05% C, 0.003-0.005% B, balance Ni.
[0014] A further technical solution is that the content of impurities O, N, and S elements in the nickel-based single-crystal high-temperature alloy is less than 5 ppm.
[0015] Secondly, the present invention provides a method for preparing the aforementioned high-stability nickel-based single-crystal superalloy, comprising the following steps:
[0016] a. Master alloy smelting: Under vacuum conditions, the raw materials are smelted according to the designed alloy composition to obtain a high-purity master alloy;
[0017] b. Preparation of single crystal test rods: The master alloy obtained in step a is cast into single crystal test rods in a single crystal furnace by spiral crystal selection method. The primary dendrite spacing of the single crystal test rods is less than 300 μm, and there are no freckles, no impurities, no small-angle grain boundaries, and the stripe R < 8°.
[0018] c. Heat treatment: The single crystal specimen obtained in step b is subjected to solution treatment and at least one stage of aging treatment.
[0019] The further technical solution is as follows: In step a, the specific operation of melting the raw materials is as follows:
[0020] First, add Co, Cr, Mo, and W elements, and heat to the first temperature range to fully melt them;
[0021] Then cool to the second temperature range and add C;
[0022] Continue cooling to the third temperature range, add Al, and hold the temperature in this range to melt it;
[0023] Then, the temperature is raised to the fourth temperature range, Ta is added, and the temperature is maintained in this range until it melts.
[0024] Finally, the temperature was raised again to the fifth temperature range, and Ti, NiB, and Hf were added. After melting, a master alloy with uniform composition was obtained.
[0025] A further technical solution is that, in step a, temperature control is achieved by controlling power, wherein:
[0026] When adding Co, Cr, Mo, and W, the power is increased to 13-15 kW to melt them;
[0027] Add C after the power is reduced to 10-11 kW;
[0028] Add Al when the power continues to drop to 8-9 kW, and gradually reduce the power to 0-1 kW;
[0029] Add Ta after increasing the power to 10-11 kW, and then gradually reduce the power to 0-1 kW;
[0030] After further increasing the power to 11-12 kW, Ti, NiB, and Hf were added.
[0031] The further technical solution is that, in step b, the spiral crystal selection method has the following process parameters: casting temperature 1510-1530℃, holding temperature 1560-1580℃, and pulling speed 3-4mm / min.
[0032] A further technical solution is as follows: in step c, the solution treatment specifically involves: heating the single crystal test rod to 1260–1280°C at a rate of 5–10°C / min and holding it at that temperature for 1–2 hours; then heating it to 1290–1305°C at a rate of 0.1–1°C / min and holding it at that temperature for 1–2 hours; finally heating it to 1305–1310°C at a rate of 0.1–1°C / min and holding it at that temperature for 1–2 hours, followed by gas quenching.
[0033] A further technical solution is that, in step c, the timeliness processing is a three-level timeliness processing, specifically including:
[0034] First-level aging: The solution-treated test bar is held at 1110-1130℃ for 2-6 hours, followed by gas quenching.
[0035] Secondary aging: The test bar after primary aging is held at 1070-1090℃ for 2-6 hours, followed by gas quenching.
[0036] Third-level aging: The test bar after second-level aging is kept at 890-910℃ for 4-8 hours, followed by gas quenching.
[0037] A further technical solution includes step d after step a and before step b: chemical composition detection and control, that is, using ICP and / or fluorescence methods to analyze the chemical composition of the master alloy, and controlling the trace elements according to the results so that the alloy composition meets the design requirements.
[0038] Thirdly, the present invention also provides a heavy-duty gas turbine blade, characterized in that the blade is made of the nickel-based single-crystal high-temperature alloy or prepared by the method described above.
[0039] Compared with the prior art, the technical effects achieved by the present invention include:
[0040] The nickel-based single-crystal superalloy with high microstructural stability provided by this invention achieves both high strength and excellent casting performance through precise proportioning of γ' phase-forming elements such as Al, Ta, and Ti with γ phase-forming elements such as Co, Cr, and W. Specifically, it exhibits a narrow solidification temperature range, fine dendritic structure, significantly reduced casting porosity (controllable below 0.08%), and effectively inhibits the formation of casting defects such as freckles and impurities. Furthermore, experiments have shown that by controlling the content of refractory elements (such as W and Mo) and avoiding the addition of Re, this invention significantly reduces the precipitation temperature of harmful TCP phases to approximately 840°C, far below the actual service temperature window, while maintaining sufficient solid solution strengthening effect. This greatly improves the long-term stability of the microstructure and effectively avoids the decrease in plasticity and early failure caused by the precipitation of brittle phases. This invention enables the alloy to achieve high-temperature mechanical properties, particularly the Larson-Miller parameter representing heat resistance and creep strength, without relying on expensive Re elements. These properties are comparable to those of traditional Re-containing second-generation single-crystal alloys and significantly superior to foreign Re-free single-crystal alloys MD2 and ReneN500. The high-stability nickel-based single-crystal superalloy provided by this invention successfully achieves a balance between low cost and high performance, providing a reliable material solution for manufacturing more competitive heavy-duty gas turbine blades.
[0041] The preparation method provided by this invention can obtain nickel-based single-crystal superalloys with low defects and high structural stability. By optimizing the melting sequence of different elements, this invention prioritizes the melting of high-melting-point elements and adds easily burnable elements such as Al and C, as well as high-density elements such as Ta and Hf, stepwise at lower power. This effectively controls element volatilization and oxidation, which helps to ensure that the content of impurities such as O, N, and S in the final master alloy is strictly controlled below 5 ppm, thereby improving the purity of the master alloy and contributing to the acquisition of low-defect, high-performance castings. The single-crystal test rods obtained by casting using the spiral crystal selection method have a primary dendrite spacing of less than 300 μm, no freckles, no impurities, no small-angle grain boundaries, and a band R < 8°, achieving high-quality single-crystal forming with dense structure and precise orientation. Attached Figure Description
[0042] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0043] Figure 1 The characteristic temperature results are for the examples and comparative examples;
[0044] Figure 2 The results of phase inversion density of the coagulated liquid in the examples and comparative examples;
[0045] Figure 3 Density results for the examples and comparative examples;
[0046] Figure 4 The results for TCP harmful phase precipitation temperature and TCP phase ratio at 950°C are shown in the examples and comparative examples.
[0047] Figure 5 Photographs of the microstructure in the as-cast and heat-treated states of the embodiment;
[0048] Figure 6 Larson-Miller curves for examples and comparative examples. Detailed Implementation
[0049] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0050] It should be understood that, when used in this specification and the appended claims, the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.
[0051] It should also be understood that the terminology used in this specification of embodiments of the invention is for the purpose of describing particular embodiments only and is not intended to limit the embodiments of the invention. As used in this specification of embodiments of the invention and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.
[0052] This invention provides a nickel-based single-crystal superalloy with high structural stability, comprising the following chemical composition by mass percentage:
[0053] 5-7% Al, 7.5-10% Co, 5-7% Cr, 0.1-0.2% Hf, 0-2% Mo, 5.5-7.5% Ta, 0-1% Ti, 8-10% W, 0.02-0.05% C, 0.003-0.005% B, balance Ni.
[0054] It should be noted that Cr and Al in the alloy composition have antioxidant properties and need to be at relatively high levels. Hf and Ta help improve casting performance, and Ta also has solid solution strengthening and precipitation strengthening effects. Without adding Re, the addition of Ta needs to be increased, but excessive Ta can easily precipitate harmful TCP phase. W is an important solid solution strengthening element. Without adding Re, the addition of W should be appropriately increased, but too high a content can easily cause TCP phase precipitation; it should be controlled at 8-10%. Co helps reduce the stacking fault energy of the alloy, thereby improving creep performance, but too high a content will lower the solid solution temperature and reduce high-temperature performance. Mo can increase the interdendritic strengthening effect. Al and Ti are γ' phase constituent elements, ensuring precipitation strengthening. In addition, Ti can also improve the alloy's resistance to hot corrosion. C helps form carbides to reduce the porosity of the alloy and provides second-phase strengthening, while B helps increase the tolerance for small-angle grain boundaries.
[0055] In some embodiments, the nickel-based single-crystal superalloy with high structural stability comprises, by mass percentage, the following chemical composition:
[0056] 5.5-6.2% Al, 8-10% Co, 5.5-6.5% Cr, 0.1-0.2% Hf, 0.5-1.5% Mo, 6-7.5% Ta, 0.5-1% Ti, 8.5-10% W, 0.02-0.05% C, 0.003-0.005% B, balance Ni.
[0057] This invention also provides a method for preparing the aforementioned high-stability nickel-based single-crystal superalloy, comprising the following steps:
[0058] a. Master alloy smelting: Under vacuum conditions, the raw materials are smelted according to the designed alloy composition to obtain a high-purity master alloy;
[0059] b. Preparation of single crystal test rods: The master alloy obtained in step a is cast into single crystal test rods in a single crystal furnace by spiral crystal selection method. The primary dendrite spacing of the single crystal test rods is less than 300 μm, and there are no freckles, no impurities, no small-angle grain boundaries, and the stripe R < 8°.
[0060] c. Heat treatment: The single crystal specimen obtained in step b is subjected to solution treatment and at least one stage of aging treatment.
[0061] In some embodiments, the process of melting the raw materials in step a is as follows:
[0062] First, add Co, Cr, Mo, and W elements, and heat to the first temperature range of 1510-1530℃ to fully melt them and complete the refining process.
[0063] Then, the temperature was lowered to the second temperature range of 1350–1400℃, and C was added.
[0064] Continue cooling to the third temperature range of 1250-1300℃, add Al, and keep it at this temperature to melt it;
[0065] Then, the temperature is raised to the fourth temperature range of 1350-1400℃, Ta is added, and the temperature is maintained in this range to melt it.
[0066] Finally, the temperature was raised again to the fifth temperature range of 1400-1450℃, and Ti, NiB and Hf were added. After melting, a master alloy with uniform composition was obtained.
[0067] In some embodiments, in step a, temperature control is achieved by controlling power, wherein:
[0068] When adding Co, Cr, Mo, and W, the power should be increased to 13-15 kW to melt them, for example, 13 kW, 14 kW, or 15 kW.
[0069] Add C after the power is reduced to 10-11 kW;
[0070] Add Al when the power continues to drop to 8-9 kW, and gradually reduce the power to 0-1 kW;
[0071] Add Ta after increasing the power to 10-11 kW, and then gradually reduce the power to 0-1 kW;
[0072] After further increasing the power to 11-12 kW, Ti, NiB, and Hf were added.
[0073] In some embodiments, in step b, the process parameters of the spiral crystal selection method are: casting temperature 1510-1530℃, holding temperature 1560-1580℃, and pulling speed 3-4mm / min.
[0074] In some embodiments, step c, the solution treatment specifically involves: heating the single crystal specimen to 1260–1280°C at a rate of 5–10°C / min and holding it at that temperature for 1–2 hours; then heating it to 1290–1305°C at a rate of 0.1–1°C / min and holding it at that temperature for 1–2 hours; finally heating it to 1305–1310°C at a rate of 0.1–1°C / min and holding it at that temperature for 1–2 hours, followed by gas quenching.
[0075] In some embodiments, step c, the timeliness processing, is a three-level timeliness processing, specifically including:
[0076] First-level aging: The solution-treated test bar is held at 1110-1130℃ for 2-6 hours, followed by gas quenching.
[0077] Secondary aging: The test bar after primary aging is held at 1070-1090℃ for 2-6 hours, followed by gas quenching.
[0078] Third-level aging: The test bar after second-level aging is kept at 890-910℃ for 4-8 hours, followed by gas quenching.
[0079] In some embodiments, after step a and before step b, step d is also included: chemical composition detection and control, that is, chemical composition analysis of the master alloy is performed using ICP and / or fluorescence methods, and trace elements are controlled according to the results so that the alloy composition meets the design requirements.
[0080] This invention also provides a heavy-duty gas turbine blade, the blade being made of the aforementioned nickel-based single-crystal high-temperature alloy, or prepared by the method described above.
[0081] The performance of the nickel-based single-crystal superalloy with high microstructure stability of the present invention is illustrated below through a specific embodiment.
[0082] This embodiment provides a nickel-based single-crystal superalloy with high microstructural stability for gas turbine blades and its preparation method. The specific composition of the alloy is shown in Table 1. For ease of comparison, the chemical compositions of comparative examples CMSX-7, MD2, and ReneN500 are also listed in Table 1.
[0083] Table 1. Composition (wt.%) of Rene N500, CMSX-7, and MD2 alloys in the Examples and Comparative Examples
[0084]
[0085] The specific preparation steps of the alloy in the example are as follows:
[0086] Master alloy smelting: Pure Al, Co, Cr, Hf, Mo, Ta, Ti, W, and NiB alloys were used as raw materials and smelted in a vacuum melting furnace according to the composition in Table 1. Before smelting, the raw materials were weighed and dried. The vacuum degree was controlled at 10°C during the smelting process. - 2 Pa. The feeding sequence and power control are as follows:
[0087] First add Co, Cr, Mo, and W, then gradually increase the power to 15.3 kW to melt them;
[0088] C was added after the power was reduced to 10.2 kW;
[0089] Add Al when the power is reduced to 8.2 kW, and gradually reduce the power to 0 kW.
[0090] After increasing the power to 8.2kW again, Ta was added, and then the power was gradually reduced to 0kW.
[0091] The power was increased back to 8.2kW by adding Ti, NiB and Hf.
[0092] The final master alloy contained 3 ppm of O, N, and S impurities, while the remaining components met the design requirements.
[0093] Preparation of single-crystal test specimens: The master alloy, after chemical composition analysis, was directionally solidified in a single-crystal furnace using a spiral crystal selection method. The casting temperature was 1520℃, the holding temperature was 1570℃, and the pulling rate was 3mm / min. The resulting single-crystal test specimens had a primary dendrite spacing of 286μm, were free of freckles, impurities, and small-angle grain boundaries, and had a stripe orientation R<8°.
[0094] Heat treatment: The single crystal specimens were subjected to solution treatment and three-stage aging treatment in a vacuum quenching furnace. Specifically:
[0095] Solution treatment: The test bar was heated to 1270℃ at 10℃ / min and held for 1h; then heated to 1300℃ at 0.1℃ / min and held for 2h; then heated to 1305℃ at 0.1℃ / min and held for 2h; finally heated to 1310℃ at 0.1℃ / min and held for 2h, followed by gas quenching.
[0096] Level 3 time limit:
[0097] First-level aging: The test bar after solution treatment was held at 1120℃ for 4 hours and then cooled by air quenching;
[0098] Secondary aging: Hold at 1080℃ for 4 hours, then air quench.
[0099] Level 3 aging: Hold at 900℃ for 4 hours, then air quench.
[0100] Performance and organizational analysis
[0101] The characteristic temperatures of the alloys in the examples and comparative examples were calculated using JMatPro software, and the results are as follows: Figure 1 As shown.
[0102] The alloy in this embodiment exhibits high γ' phase precipitation temperature and initial melting temperature, with a heat treatment window of 40°C, comparable to other low-Re second-generation single-crystal high-temperature alloys, higher than ReneN500, and significantly higher than CMSX-7. This indicates that the alloy of this invention maintains high strength at high temperatures and is easily controllable in terms of microstructure. The mushy region is 55°C, lower than ReneN500 and CMSX-7, indicating that the alloy of this invention is less prone to eutectic formation during casting.
[0103] Figure 2 The solidification phase inversion density shows that the alloy of the present invention is much lower than the other three alloys, indicating that the alloy of the present invention is less prone to freckle defects during casting and has excellent casting performance.
[0104] Figure 3As for the alloy density results, the alloy density of the embodiments of the present invention is lower than that of all comparative examples, which helps to reduce the centrifugal force on the blades and turbine disks during the operation of the gas turbine, further reducing failures caused by excessive stress and improving service reliability.
[0105] Tissue stability comparison of the examples and comparative examples Figure 4 As shown, the precipitation temperature of harmful TCP phase in the alloy of the example is lower than the service temperature of the alloy (above 950°C), only 840°C, which is much lower than that of the comparative example, showing excellent long-term stability of the microstructure.
[0106] The microstructure of the alloy in the as-cast and heat-treated states as shown in the example Figure 5 As shown in the figure, the porosity of the example in the as-cast state was less than 0.08%, and there was no increase in porosity after heat treatment, which is significantly lower than the porosity of other low-Re alloys (above 0.18%). The primary dendrite spacing was only 286 μm; the eutectic ratio in the as-cast state was 3.9%, and most of the eutectic was eliminated after heat treatment; the γ′ phase size in the heat-treated state was 609 nm. The microstructure of the example before and after heat treatment is similar to that described above. Figure 1-4 The analysis results are consistent, indicating that the single-crystal alloy provided by this invention is easy to cast, has few defects, good heat treatment response, is not prone to precipitation of harmful phases, and has high structural stability.
[0107] Larson-Miller curves for the examples and comparative examples are as follows: Figure 6 As shown in the figure, the Larson-Miller curves indicate that the creep performance of the alloys in the examples is ranked as follows: Example > MD2 > Rene N500. Under low temperature and high stress, the performance of the examples is higher than CMSX-7, while under high temperature and low stress, it is slightly lower than CMSX-7. This demonstrates that the single-crystal alloys provided by this invention generally meet the high-temperature operating requirements of gas turbine blades.
[0108] In summary, this embodiment successfully prepared a Re-free nickel-based single-crystal high-temperature alloy with stable structure, excellent casting performance, low density, and high-temperature performance through reasonable composition design and strict process control. Its comprehensive performance is superior to existing similar Re-free alloys and it has good prospects for engineering applications.
[0109] The above description describes specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A nickel-based single crystal superalloy having high microstructural stability, characterized in that, by mass, comprising the following chemical components: 5-7% Al, 7.5-10% Co, 5-7% Cr, 0.1-0.2% Hf, 0-2% Mo, 5.5-7.5% Ta, 0-1% Ti, 8-10% W, 0.02-0.05% C, 0.003-0.005% B, and the balance of Ni.
2. The single crystal nickel-base superalloy with high microstructural stability of claim 1, wherein, by mass, comprising the following chemical components: 5.5-6.2% Al, 8-10% Co, 5.5-6.5% Cr, 0.1-0.2% Hf, 0.5-1.5% Mo, 6-7.5% Ta, 0.5-1% Ti, 8.5-10% W, 0.02-0.05% C, 0.003-0.005% B, and the balance of Ni.
3. The single crystal nickel-base superalloy with high microstructural stability of claim 1, wherein, The content of impurities O, N, and S in the nickel-based single crystal superalloy is less than 5 ppm.
4. A method of producing a nickel-based single crystal superalloy with high microstructural stability according to any one of claims 1 to 3, characterized in that The method comprises the following steps: a. Master alloy smelting: under vacuum conditions, raw materials are smelted according to the designed alloy composition to obtain a master alloy with high purity; b. Single crystal test rod preparation: the master alloy obtained in step a is cast into a single crystal test rod through a spiral selection method in a single crystal furnace, the single crystal test rod has a primary dendrite spacing of less than 300 μm, no freckle, no foreign crystal, and no low-angle grain boundary, and a strip R of less than 8°; c. Heat treatment: the single crystal test rod obtained in step b is subjected to solid solution treatment and at least one level of aging treatment.
5. The method of claim 4, wherein, In step a, the operation of smelting the raw materials is as follows: Co, Cr, Mo, and W are first added, and the temperature is raised to a first temperature interval to fully melt them; C is then added after the temperature is lowered to a second temperature interval; Al is added after the temperature is continuously lowered to a third temperature interval, and the temperature is maintained in this interval to melt Al; Ta is then added after the temperature is raised to a fourth temperature interval, and the temperature is maintained in this interval to melt Ta; Ti, NiB, and Hf are finally added after the temperature is raised to a fifth temperature interval, and the master alloy with uniform composition is obtained after melting; In step a, temperature control is achieved by controlling power, wherein: Co, Cr, Mo, and W are melted by raising the power to 13-15 kw; C is added after the power is lowered to 10-11 kw; Al is added when the power is continuously lowered to 8-9 kw, and the power is gradually lowered to 0-1 kw; Ta is added after the power is raised to 10-11 kw, and the power is gradually lowered to 0-1 kw; Ti, NiB, and Hf are added after the power is raised to 11-12 kw again.
6. The method of claim 4, wherein, In step b, the spiral selection method has the following process parameters: a casting temperature of 1510-1530 ℃, a holding temperature of 1560-1580 ℃, and a pulling rate of 3-4 mm / min.
7. The method of claim 4, wherein, In step c, the solid solution treatment is as follows: the single crystal test rod is raised to 1260-1280 ℃ at a rate of 5-10 ℃ / min, maintained for 1-2 h, then raised to 1290-1305 ℃ at a rate of 0.1-1 ℃ / min, maintained for 1-2 h, and finally raised to 1305-1310 ℃ at a rate of 0.1-1 ℃ / min, maintained for 1-2 h, and then air quenched.
8. The method of claim 4, wherein, In step c, the aging treatment is a three-level aging treatment, which specifically comprises: Primary aging: the test bar after solution treatment is kept at 1110-1130 ℃ for 2-6 h, and then air quenched; Secondary aging: the test bar after primary aging is kept at 1070-1090 ℃ for 2-6 h, and then air quenched; Tertiary aging: the test bar after secondary aging is kept at 890-910 ℃ for 4-8 h, and then air quenched.
9. The method of claim 4, wherein, After step a and before step b, there is also step d: chemical composition detection and regulation, that is, the chemical composition of the master alloy is analyzed by ICP and / or fluorescence method, and the trace elements are regulated according to the results, so that the alloy composition meets the design requirements.
10. A heavy-duty gas turbine vane characterized by, The blade is made of the nickel-based single crystal superalloy according to any one of claims 1-3, or is prepared by the method according to any one of claims 4-9.
Citation Information
Cited By
Fluorescence defect root control method and system after turbine blade grinding
CN122113313A
A method of controlling the N content in a polycrystalline high-temperature alloy to suppress TCP phase precipitation
CN122382397A
